1999
DOI: 10.1046/j.1365-246x.1999.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Clockwise rotations recorded in Early Cretaceous rocks of South Korea: implications for tectonic affinity between the Korean Peninsula and North China

Abstract: Recent interest has focused on whether South Korea may have undergone variable tectonic rotations since the Cretaceous. In an effort to contribute to the answer to this question, we have completed a palaeomagnetic reconnaissance study of Early Cretaceous sedimentary and igneous rocks from the Kyongsang basin in southeast Korea. Stepwise thermal demagnetization isolated well-defined characteristic magnetization in all samples. The palaeomagnetic directions reveal patterns of increasing amounts of clockwise (CW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 43 publications
2
45
1
Order By: Relevance
“…A third probable contributor would be far-field expressions of the India-Asia collision (Acton and Gordon 1989;Besse and Courtillot 1991;Vandamme et al 1991;Leech et al 2005). As initially proposed by Zhao et al (1999), the Kula-Eurasia collision may influence the vertical rotations of the Korean Peninsula.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A third probable contributor would be far-field expressions of the India-Asia collision (Acton and Gordon 1989;Besse and Courtillot 1991;Vandamme et al 1991;Leech et al 2005). As initially proposed by Zhao et al (1999), the Kula-Eurasia collision may influence the vertical rotations of the Korean Peninsula.…”
Section: Discussionmentioning
confidence: 91%
“…However, earlier paleomagnetic studies on Mesozoic to Tertiary rocks from the Korean Peninsula showed vertical rotations with respect to China (e.g., Lee et al 1987;Kim and Van der Voo 1990;Doh and Piper 1994;Zhao et al 1994Zhao et al , 1999Doh et al 1999Doh et al , 2002Lee et al 1999;Zhao et al 1999;Uno 2000;Park et al 2003Park et al , 2005Park et al , 2007Kim et al 2009). Then, viable solutions to explain the various degrees of vertical rotations observed in previous paleomagnetic investigations required that individual geologic terranes of the Korean Peninsula formed in Mesozoic to Tertiary experienced different degrees of vertical rotations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…• ; Zhao et al, 1999) is statistically indistinguishable from the remagnetized direction of Cretaceous age (D = 58.8…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the same experiment was newly performed on a sample of primary magnetization from the Doh and Piper, 1994;Doh et al, 1997;Lee et al, 1999;Zhao et al, 1999). Nogam Formation in the central part of the Bagjisan Syncline (Uno, 1999).…”
Section: Discussionmentioning
confidence: 99%